Monitoring treatment response in metastasic colorectal cancer: Economic evaluation of PrediCTC versus computed tomography scan. (July 2019) - Antón Rodríguez, Cristina; Abal Posada, Miguel; Alonso Alconada, Lorena; Candamio Folgar, Sonia; López López, Rafael; Martín-Saborido, Carlos
Background: Late state colorectal cancer treatments have important side effects that should be avoided in patients where drug effectiveness is not adequate. PrediCTC is a new biomarkers blood test developed to determinate the chemotherapy response in unresectable metastatic colorectal cancer patients that could allow to obviate unnecessary treatments. Aim: To assess from the Spanish Societal Perspective the cost-utility of the test PrediCTC compared to the computed tomography in aim to evaluate chemotherapy treatment response in late stage colorectal cancer patients. Methods: Based on the results of Barbazán et al., a Markov model has been developed, in which the different lines and cycles that the colorectal patient can receive and how they can move between them according to the computed tomography or PrediCTC have been represented. The effectiveness has been expressed in quality adjusted life years (QALYs), avoiding adverse events. Results: Base case analysis shows savings in different types of costs for PrediCTC (per patient): €14.30 in those arise from adverse events, €22, 345.73 in chemotherapy costs, €4849.61 in other direct costs, and €306.21 in indirect costs. Although computed tomography 12-week assessed patients gain 0.17 QALYs compared with PrediCTC. Conclusions: From the Spanish Societal Perspective, PrediCTC is not a cost-utility option but allows to identify earlier patients who are not benefiting from first-line chemotherapy avoiding unnecessary side effects and costs.